Real-world implementation and adaptation to local settings of first trimester preeclampsia screening in Italy: a systematic review - Silvia Amodeo; Giulia Bonavina; Anna Seidenari; Paolo Ivo Cavoretto; Antonio Farina (Clinical and Experimental Obstetrics & Gynecology)
Background: Preeclampsia (PE) is a multisystem disease of pregnancy representing a major cause of maternal and perinatal morbidity and mortality. Early identification of pregnancies at risk of developing PE is crucial for implementing preventive strategies. The effectiveness of PE screening in the first trimester is widely recognized and endorsed by several guidelines, but unfortunately real-world implementation of this practice within local settings remains difficult. Methods: We performed a systematic review of the literature to understand the critical issues hampering the implementation of PE screening procedures in Italy. All studies on first trimester PE screening in the Italian population were eligible for inclusion. Key-concepts relevant for implementation of PE screening in Italy were extracted and analysed qualitatively. Results: Nine articles were selected and included. Lack of evidence concerning the topic of PE screening in Italy was shown. Major critical issues found encompassed health-care personnel education, training of sonographers, economic coverage for biochemical markers and adjustment of algorithms based on population characteristics. Conclusions: Identification and adaptation of specific protocols to local settings and population characteristics is critical for successful implementation of early PE screening in Italy. This process has the potential to improve pregnancy outcomes and to save valuable health-care resources, particularly scarce in the COVID-19 era. There is an urgent need for research studies on specific local populations focussing on subtle details capable of maximizing PE screening uptake. This action will likely potentiate PE screening implementation reducing the burden and the cost of perinatal and maternal complications.